New College Students’ Shyness and Academic Performance : Some Strategies to cope with shyness -A case Study conducted at Faculty of Education, Misurata University - Widad Mahmoud Ben Raba’a (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
The main aim of this study is to examine the effects of shyness on new college students and to explore effective strategies to overcome it. The research seeks to answer two key questions: How does shyness affect students’ academic performance and social interactions? And what strategies do students use to cope with or overcome shyness? A descriptive quantitative design was employed using a structured questionnaire consisting of 14 closed-ended statements. The questionnaire was divided into two parts: six items focused on situations where students experience shyness, and eight items on strategies to manage shyness. The sample included 62 randomly selected first-semester English major students at the Faculty of Education, Misurata University. Data were analyzed using frequency counts and percentages to identify common patterns in students’ experiences of shyness and the coping mechanisms they employ. Results showed that many students feel shy when speaking in front of professors and participating in class discussions, negatively impacting their academic engagement and social interactions. Nonetheless, several strategies such as communication skills improvement-applying communicative language teaching approaches, cultivating peer support, relaxation techniques, and regular practice were identified as effective in overcoming shyness. These findings highlight the importance of addressing shyness to support students’ academic success and social adjustment in the university environment.